2011
DOI: 10.1089/jwh.2011.2765
|View full text |Cite
|
Sign up to set email alerts
|

Women's Knowledge and Awareness of Gynecologic Cancer: A Multisite Qualitative Study in the United States

Abstract: Participants lacked critical knowledge needed to understand their gynecologic cancer risk and seek appropriate care. Pap tests and routine examinations offer ideal opportunities to educate women about the purpose of the Pap test as well as risk factors and symptoms associated with various gynecologic cancers. The reported influence of the mass media also supports the viability of multimedia educational strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 30 publications
2
40
1
5
Order By: Relevance
“…The studies indicate that women have lack of knowledge regarding the scanning tests, the frequency of having tests and the purpose of having the tests (Abothchie ve Shokar, 2009;Al-Sairafi, 2009;Nakaluvu, 2009;Phongsavan et al, 2010;Chigbu ve Aniebue, 2011;Cooper et al, 2011;Hawkins et al, 2011;Mbamara et al, 2011;Minchev et al, 2011;Paolino et al, 2011). More than half of the women in our study think that they should take pap smear test only when they have gynecological disorders.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The studies indicate that women have lack of knowledge regarding the scanning tests, the frequency of having tests and the purpose of having the tests (Abothchie ve Shokar, 2009;Al-Sairafi, 2009;Nakaluvu, 2009;Phongsavan et al, 2010;Chigbu ve Aniebue, 2011;Cooper et al, 2011;Hawkins et al, 2011;Mbamara et al, 2011;Minchev et al, 2011;Paolino et al, 2011). More than half of the women in our study think that they should take pap smear test only when they have gynecological disorders.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, a large group of them know that bleeding like spotting after instrumental sexual activities and intercourse is a symptom of cervical cancer. Despite it is known that unaccountable vaginal bleeding is a risk factor for cervical cancer, the symptoms of other cancer types may not have been known commonly (Phongsavan et al, 2010;Cooper et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a clear message promoting screening for ovarian, uterine, vaginal, and vulvar cancers can be frustrating both for women who await the development of effective screening strategies and for the medical and public health communities that lack evidence-based tools to prevent and detect early disease. 8 All these factors underscore an important need to educate and communicate with women and healthcare providers about gynecologic cancer.…”
Section: Campaign Challenges and Opportunitiesmentioning
confidence: 99%
“…[9][10][11][12] Previous studies have reported that women do not know the purpose of a Pap test and believe that it screens for multiple gynecologic cancers, sexually transmitted diseases (STDs), and other conditions. [8][9][10][11][12][13] Recent discussions among healthcare providers have also questioned the need and purpose of the pelvic examination. 14,15 Knowledge among women about symptoms related to gynecologic cancers also is lacking.…”
Section: Campaign Challenges and Opportunitiesmentioning
confidence: 99%